Couching as Technology and Effective Way of Personnel Development in Commercial Organization - A. L. Barannikov; L. E. Zhuravleva; T. A. Levochkina (Вестник Российского экономического университета имени Г. В. Плеханова)
According to executives and business proprietors, current methods of company management are losing efficiency, which is especially evident in conditions of quickly changing world and growing information flows. Today the majority of companies are facing problems of searching for new resources in order to raise efficiency both on individual and organizational level. It is a historical fact that in the conventional pattern of business there are three basic components: people, processes and communications. This triad made up the foundation of any business for a long time. However, now it is clear that it is insufficient for effective company management. Topicality of the research subject is stipulated by dynamic nature of today’s market. Certain qualification is required for successful adjustment to continuous changes. Thanks to efficient system of personnel management we can provide sustainable implementation of objectives and goals of the company. The article studies the essence, key methods, methodology, approaches and tools of the process of HR management and couching, illustrated by the concrete enterprise and gives recommendations on upgrading the system of HR management. Types of recruiting agencies in Russia and technologies of their work are investigated.